The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1177/1359183512442629
|View full text |Cite
|
Sign up to set email alerts
|

Cod, curtains, planes and experts: Relational materialities in the museum

Abstract: Museums are sites where people encounter material objects. This article examines object and subject entanglements that take place at a university museum in northern Norway, and illustrates how objects shift identities as they interact with subjects and how subjects are also affected by the encounter. A relational materialities perspective, which demonstrates how object identity is related to the subject it engages with, allows multiple versions of objects to appear. Working as a certified expert in the univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In the museum context, an individual's preexisting, ontological perspectives can influence which identity of an object will be enacted. According to Maurstad (2012), It is a type of knowledge politics performed by subjects in direct material engagement with things, but without clear political intent. The politics is situated in practices, procedures and rules of engagement between entities.…”
Section: Politicsmentioning
confidence: 99%
“…In the museum context, an individual's preexisting, ontological perspectives can influence which identity of an object will be enacted. According to Maurstad (2012), It is a type of knowledge politics performed by subjects in direct material engagement with things, but without clear political intent. The politics is situated in practices, procedures and rules of engagement between entities.…”
Section: Politicsmentioning
confidence: 99%
“…In return, as museum objects, they become part of collections, research, and communication. Situated in mutually constitutive relations with museum expertise, they perform versions of the world (Maurstad 2012). Even house-museums, which endeavor to avoid physically de-contextualizing museum materiality from its former relations by preserving the "original assemblages" (Young 2007:73) and "the lived context of the commemorated life" (Hancock 2010:14), work to tell stories that were not told by the previous inhabitants in everyday life.…”
Section: Musealization Practices and Second Homesmentioning
confidence: 99%
“…Researchers have also analyzed the significance of objectexpert entanglements to the constitution of knowledge in museums (e.g. Mordhorst 2009;Maurstad, 2012) and have found that complex interplays between discursive and material elements knit museum exhibitions together (e.g. Macdonald 2002;Yaneva, 2003).…”
Section: Musealization Practices and Second Homesmentioning
confidence: 99%
“…Within the last twenty years, curation studies have drawn attention to the growing and combined importance of new technology, new constituencies, and new ways of thinking about the role of museums in society (Dubuc ; Thomas, ). As a consequence, attention has shifted from older debates about which objects should and should not be conserved within museum collections (Etherington ; Welsh ) to broader deliberations on the role and geographies of curation in an interconnected and relational society (Cairns ; Dubuc ; Hooper‐Greenhill ; Maurstad ). For example, Peers and Brown () saw the museum as a curatorial “contact zone”, defined as a place that source community members and other stakeholders enter for consultation, collaboration, and conflict resolution over issues such as storage, conservation, and access.…”
Section: Introductionmentioning
confidence: 99%